Isolation and Characterization of Dental Pulp Stem Cells from a Patient with Papillon-Lefevre Syndrome - YARAT, AYŞEN; AKYÜZ, SERAP HATİCE; TAPŞIN GÜLLÜOĞLU, SIDIKA (ELSEVIER SCIENCE INC, 2013)
Introduction: Papillon-Lefevre syndrome (PLS) is a rare autosomal recessive disorder. characterized by immune dysregulation because of a mutation in cathepsin c gene, resulting in hyperkeratosis of the palms, soles, elbows, and knees combined with premature loss of the primary and permanent dentitions. Periodontal tissue abnormalities in PLS patients were reported previously. However, less is known about dental pulp tissue derived cells of PLS patients. This study aimed to show stem cell potential of PLS dental pulp stem cells (DPSCs) and provide new evidence regarding the pathophysiology of the disease. Methods: DPSCs were characterized by using flow cytometry and immunocytochemistry. They were also induced to differentiate into adipogenic, osteogenic, chondrogenic, odontogenic, and myogenic cells. Results: The results revealed that PLS DPSCs are stained positive for mesenchymal stem cells surface markers CD29, CD73, CD90, CD105, and CD166. PLS DPSCs were able to differentiate into adipogenic, osteogenic, chondrogenic, and odontogenic cell types properly. PLS DPSCs expressed embryonic stem cell markers Oct4, Sox2, cMYc, and Klf4 and showed similar proliferation rate compared with DPSCs isolated from healthy young controls. Interestingly, it was found that unlike the healthy DPSCs, PLS DPSCs are not able to form myotubes with correct morphology. Conclusions: These data are being reported for the first time; therefore, they might provide new insights to the pathology of the disease. Our results suggest that the PLS DPSCs might be an autologous stem cell source for PIS patients for cellular therapy of alveolar bone defects and other dental tissue-abnormalities observed in PLS. (J Endod 2013;39:31-38)
Keywords: Dental pulp cells; differentiation; Papillon-Lefevre syndrome; stem cells; BONE-MARROW; ODONTOGENIC DIFFERENTIATION; STROMAL CELLS; IN-VITRO; TISSUE; PROLIFERATION; EXPRESSION; SCAFFOLD